Digitalization Meets Circular Economy - Zimmermann, Hans-Dieter (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This paper examines the role of digitalization in the implementation of the circular economy (CE). It shows that the circular economy can be seen as a tool for sustainability and that digitalization is a key driver for its implementation. The links between the circular economy and digitalization are shown and the concept of the digital circular economy is presented based on a narrative literature analysis. The Smart CE framework and the Digital Function for Circular Economy (DF4CE) framework are presented. The DF4CE framework links digital functions to the 10 R strategies of the circular economy. It derives seven mechanisms for how digital functions can improve the circular economy, including recycling, reuse and reduction. The paper emphasizes that further empirical research and practical guidelines are needed for the further development of the digital circular economy.